FOCAL CORTICAL DYSPLASIAS: CLINICAL AND ELECTRO-NEUROIMAGING CHARACTERISTICS - K. Yu. Mukhin (Русский журнал детской неврологии)
In spite of a notable advance made in epileptology, resistant epilepsies account for approximately 30 % of all forms of epilepsy particularly in patients with focal seizures. One of the main causes of therapy-resistant focal epilepsies is focal cortical dysplasias (FCD). This term was first introduced by D. Taylor et al. in 1971. FCD belongs to abnormal cortical development. Among all abnormalities of cortical development, FCD in surgically treated children amounts to 75 %. FCD is the most common cause of resistant epilepsy in children and the most frequent reason for diagnosing cryptogenic focal epilepsy with intractable seizures. The author gives a detailed literature review dedicated to FCD as a cause of resistant epilepsy, including the classification and histologic characteristics of FCD, its clinical manifestations and prognosis, and approaches to medical and surgical treatments.